Phytodiversity and morpho-anatomical modification of the wild plants irrigated by tannery effluents - Sahar Naveed; Peter Olusakin Oladoye; Syeda Sadaf Zahra; Mansoor Hameed (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background With the rapid increase in industrialization, irrigation through waste or sewage water is a common practice due to low and scarce freshwater supply. Plants are exposed to hazardous metals that accumulate in plant tissues and negatively affect them. Therefore, current study aimed to investigate the phytodiversity and morpho-anatomical modification of wild plants irrigated by tannery effluents. Six wild plant species were collected from different sites of Multan near tannery industries through the quadrate method. Results Results indicated that Cynodon dactylon L. had the highest relative cover, relative frequency, relative density, and important index value, i.e., 35, 10, 30, and 75% followed by other species. The morpho-anatomical modifications showed a reduction in leaf characteristics in C. dactylon, Eragrostis barrelieri Daveau, Polypogon monpeliensis L., Solanum nigrum L., Triticum aestivum L., except in Asparagus adscendens Roxb. A decrease in leaf length was observed in all species with maximum reduction of 55% in T. aestivum followed by P. monpeliensis. Similarly, reduction in metaxylem area was observed in T. aestivum, whereas sclerenchymatous thickness found to increase in P. monpeliensis by 15%. Asparagus adscendens showed decrease by 70% in comparison to other species. Conclusion Variation in the trend of the morpho-anatomical parameters as well as phytodiversity helps to understand the tolerance potential of the wild plants under wastewater irrigation released by tannery industries and that adverse developmental features in wild plants could be used as bioindicators of toxic heavy metal pollution.